Analisa Kemacetan Lalu Lintas Pada Ruas Jalan Dengan Deterministic Queuing Analysis - Herawati, Herawati; Mutharuddin, Mutharuddin (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
One of the phenomena of transportation problem currentl.y is the congestion which cxrurs at highwaybottlenecks. Congestion is detennined btJ the low capacity at the bottleneck point compared to theentrance rood segment before the bottleneck. This capacity reduction can be inft d by the decrease inthe number of traffic lanes, the reduced width of rood shoulders and traffic signs.Location of the study is on a signaHzed intersection (MT Haryano Street) and unsignalized intersection(Cilincing Street). Traffic congestion Analysis is caused bi; the bottleneck based on the principle dinamictraffic with deterministic queuing method (DQA).There are three point of conclusion based on the analysis is determined queuing length, the queuing rate,Physical. diagram discharging. Firstly, queuing length are in the signalized intersection is 5.98 km andunsignalized intersection is 38.01 km. Secandl.y, queuing rate of rehicles produced by the method DQAat signalized intersection of 10,075 pcu smaller than the maximum cumulative volume at the intersection(19,900 pcu). Finally, Pln;siml diagram discharging rate is means when congestion cxrurs untilqueue missing (during t2). The Physical. diagram discharging rate at signalized intersection is 19.01km;hour and unsignalized intersection is only 4.15 km/ hour. From those amclusions show the queueinglength will increase the queuing rate and reduce congestion at the existing speed.